Analise da espinheira santa (MaytenusilicifoliaMartiusexReissek) como inibidor de corrosão orgânico para aplicação em fluidos para completação e seu estudo de adsorção no processo - Paiva, Jardel Hugo Gonçalves (Universidade Federal Rural do Semi-Árido, 2020)
The corrosive process is an evil that directly affects all the socio-economic sectors of a country, thus regardless of the space in which this deterioration occurs, whether in a rural, urban, industrial, or even marine environment, corrosion contributes significantly to the emergence a series of harmful factors for the well-being of society, as well as in relation to natural resources. The espinheira-santa (Maytenus ilicifolia Martius ex Reissek) is one of the few herbal medicines that have pharmacological effects proven by the Medication Center (CEME) of the Ministry of Health of Brazil, among these effects, the antiulcerogenic activity stands out, thus having total security of its use. In this regard, there are several researches for natural organic compounds acting as inhibitors, due to some advantages such as: being considered low cost, non-toxic, and mainly being acceptable from an ecological point of view. Completion fluid is, by definition, a solids-free solution, which may be saline, inverted emulsions and low solids oil, it must be able to control surface pressures with varying density, be stable at well temperature , as well as not trapping gas easily. The objective of the present work is to analyze the use of Espinheira Santa as a potential inhibitor of green corrosion, and thus verify its parameters of efficiency and optimization in the extraction process, as well as to evidence the study of adsorption of this plant in the corrosion processes carried out, for this, its application in saline fluids was used. The tests carried out were for 50, 100 and 150 lb / gal of concentration of this salt, the dosage parameter of organic inhibitor being varied, with these concentrations being 0.2, 0.4, 0.6, 0.8, 1, 2 and 3% holy espinheira extract. The results obtained led to the conclusion that the extract of the plant in question had low efficiency, when added in small concentrations, however as its dosage increased there was a linear increase in its efficiency and a notable reduction in the corrosive rate. In this context, for a less aggressive medium, in the case of a fluid with a concentration of 50 lb / gal, better inhibition efficiencies were obtained, reaching up to 93%, however as the medium became more aggressive, this efficiency in passivating the cell decreases, with the maximum values being 92% for 100 lb / gal and 88% for 150 lb / gal, obviously considering the use of 30000 ppm of the studied extract. Thus, as expected in practice, the presence of a more degrading medium to the material results in a decrease in absolute values of efficiency, although this gradual increase and its potential passivation power are always observed.
Monografia
Keywords: Inibidor de corrosão; Espinheira santa; Fluido de completação; Corrosion inhibitor; Espinheira santa; Completion fluid; ENGENHARIAS::ENGENHARIA DE PETROLEO